2004
DOI: 10.1074/jbc.m306217200
|View full text |Cite
|
Sign up to set email alerts
|

Xenopus Death Receptor-M1 and -M2, New Members of the Tumor Necrosis Factor Receptor Superfamily, Trigger Apoptotic Signaling by Differential Mechanisms

Abstract: Signaling through the tumor necrosis factor receptor (TNFR) superfamily can lead to apoptosis or promote cell survival, proliferation, and differentiation. A subset of this family, including TNFR1 and Fas, signals cell death via an intracellular death domain and therefore is termed the death receptor (DR) family. In this study, we identified new members of the DR family, designated xDR-M1 and xDR-M2, in Xenopus laevis. The two proteins, which show high homology (71.7% identity), have characteristics of the DR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 48 publications
(60 reference statements)
0
25
0
Order By: Relevance
“…While death induced by expression of the death domain of xDR-M2 is blocked by inhibition of caspase-8, death induced by expression of the death domain of xDR-M1 is blocked by serine protease inhibition. 37 Our data indicate that the apoptotic pathway activated by nuclear TRADD does not require caspase-8 or caspase-2. Instead, death is dependent upon caspase-9, which must have an intact catalytic site and be able to form dimers.…”
Section: Discussionmentioning
confidence: 67%
“…While death induced by expression of the death domain of xDR-M2 is blocked by inhibition of caspase-8, death induced by expression of the death domain of xDR-M1 is blocked by serine protease inhibition. 37 Our data indicate that the apoptotic pathway activated by nuclear TRADD does not require caspase-8 or caspase-2. Instead, death is dependent upon caspase-9, which must have an intact catalytic site and be able to form dimers.…”
Section: Discussionmentioning
confidence: 67%
“…[20][21][22][23] The TR-regulated aspects of metamorphosis include programmed cell death; however, little is known about the intracellular pathway that is involved in the apoptotic signal elicited by the TR-T 3 complex. To investigate whether DR signaling is involved in the metamorphosis of X laevis, we previously isolated and analyzed the death receptor (DR) members xDR-Ms 24 and xTNFR1, and a DR ligand, xTNF-␣. 25 We found that xTNF-␣ attenuates the T 3 -induced apoptosis of a X laevis endothelial cell line, Xlgoo, probably through its receptor, xTNFR1.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, death receptor ligands could function in a paracrine/autocrine way, making them potential useful tools for the rapid and coordinated elimination of complex tissues (Kavurma and Khachigian, 2003). Two Xenopus death receptors, xDR-M1 and xDR-M2, have been identified recently (Tamura et al, 2004). As xDR-M1 and xDR-M2 have been shown to induce apoptosis by activation of a serine protease(s) and caspase-8, respectively, it will be of great interest to investigate the possible role of xDR-M2 in the metamorphic apoptotic pathway.…”
Section: Bid Is Cleaved By Caspase 8 During Tail Regressionmentioning
confidence: 99%